Uji Aktivitas Antioksidan Sediaan Face Mist Ekstrak Kulit Buah Naga Merah (Hylocereus Polyrhizus) - Muzayanah, Fatimatul; Saraswati, Maulita; Supriyanto (Pratama Medika : Jurnal Kesehatan, 2024)
Dragon fruit skin contains compounds that can be useful as antioxidants such as betalain and anthocyanin. The amount of high antioxidant content of red dragon fruit skin is able to slow, delay, or prevent the occurrence of free radical reaction processes that make humans experience premature aging. Face mist temasuk in cosmetic skin freshener that serves to refresh the facial skin, remove the remaining oil from the skin that may still exist, as well as deinfekta mild and at the same time can help cover the pores back. This study was conducted to develop red dragon fruit skin extract (Hylocereus polyrhizus) Face mist preparation as an antioxidant with a variant concentration of red dragon fruit skin extract (Hylocereus polyrhizus).Red dragon fruit skin extract (Hylocereus polyrhizus) using maceration extraction process, then extract with concentration variants 1%, 2%, 3% prepared face mist. Vitamin C as positive control and base face Mist as negative control. After obtained comparison of data processed statistically with one-way ANOVA using SPSS 22.Face mist preparation red dragon fruit skin extract (Hylocereus polyrhizus) has antioxidant activity.3% concentration of face mist preparation red dragon fruit skin extract (Hylocereus polyrhizus) contains the highest antioxidant.